Fertility after Successful Use of the B-Lynch Uterine Compression Suture in Atonic Postpartum Hemorrhage during Cesarean Delivery - Intapibool, Suntorn (Journal of Health Science of Thailand, 2020)
The present study described the patient with acute postpartum hemorrhage (PPH) due to the uterine atony during the cesarean section. The author presented the success of the next pregnancy after compression suture the uterus with the B-Lynch technique. Acute PPH caused by the uterine atony, which happened both times in the same patient, was monitored for quick diagnosis and proper treatment to prevent the adverse event. The uterine compression suture should be an attempt to preservative uterus. The B-Lynch suture’s advantage was applied too quickly, safely, and preserved reproductive health status. This procedure should be trained for general obstetricians.